Enhancing student’s creativity in architectural design by learning from the design cognitive process of a prominent architect - Abdul Rahman Khamaruzaman,; Salahuddin Abdul Hakeem Abas,; Ahmad Faiz Hassan Naziri,; Ismail Samsuddin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Architecture is a professional discipline that integrates art and science to build attractive, practical and safe structures for human activities. In architecture, design is a core subject where students are taught the main skills to produce drawings and models of building design. Furthermore, architectural design involves a cognitive process that generates higher level of creativity in producing noble design solution. Such process is also fundamental to students who are learning architecture in the higher education. It helps student to develop their level of creativity and competency in design. This intellectual capability is an important aspect for architectural students to practice as professional architect when they graduated. Malaysia has many talented and internationally well-known professional architects. Their works represent high level of creativity that can be beneficial sources of practical knowledge to the students. Unfortunately, these respectable architects’ creative cognitive processes are not properly documented for references to others within the architectural community. Therefore, this paper aims at exploring and identifying the cognitive process characteristics of a local prominent, visionary architect, Dato’ Dr Ken Yeang who is well known for his creative, masterpiece architectural works. A semi-structured interview was conducted to gather insights on his cognitive process while designing to produce creative solution for complex architectural problems. The study found that this professional architect has a distinct formulation of knowledge, skills, attributes and principles that he utilises while designing and looking for creative solutions. This dynamic, integrated process involves imagination (intrinsic) and modelling(extrinsic) capabilities that produce renowned local architectural buildings. Such significant cognitive attributes will be useful guides to improve creativity in design among the young architectural students.